Effect of Online Systems Quality, Banking Service Product Quality and Customer Trust on the Success of BRI Syari'ah E-Banking Information System - Karmawan Karmawan; Suhaidar Suhaidar (Integrated Journal of Business and Economics (IJBE), 2019)
This study will discuss and to find out and test whether Online Systems Quality, Banking Service Product Quality and Customer Trust are thought to influence the Success of E-Banking Information System in one of the Shariah Banks in Pangkalpinang City. This research is quantitative research, using primary data, the instrument used is a questionnaire given to respondents. The population in this study is the Customer of BRI Bank Syari'ah PangkalPinang Branch, while the sampling technique used is convenience sampling technique. The data of this study will be processed and analyzed by Multiple Linear Regression tests with the aim to find out how far the knowledge and level of understanding of Online Systems Quality, Banking Service Product Quality and Customer Trust are thought to influence the success of E-Banking Information System in BRI Sharia Banks in Pangkalpinang.